Análise retrospectiva de casuística de hernioplastia inguinal videolaparoscópica TAPP - Furtado, Marcelo Lopes [UNESP] (2015)
Introduction: The inguinal hernia is the most common form of hernias of the abdominal wall and its surgical repair, after appendectomy, is the most performed surgery by the General Surgeon. It is estimated that are held about 20 million operations/year in the world. The modern techniques of inguinal hernia repair seek to improve the quality of life of patients, decreasing the rates of recurrence and chronic pain through tension-free prosthesis repair. The development of laparoscopy in the last two decades, rescued the importance of inguinal hernia and its treatment to the General Surgeon. The aim of this study was to analyze 829 cases of Transabdominal Pre peritoneal inguinal hernia repair (TAPP) and compare it to the results of the literature emphasizing chronic pain, complications and recurrence rate. Method: retrospective study of 616 patients undergoing laparoscopic inguinal hernia repair by TAPP by the same surgeon in private hospital, during the period between June 1996 and June 2010. All patients were reassessed on the 10th and 30th day of post-operative and followed later with 6, 12 and 24 months. Results: the predominant sex was male with 575 (93.3%) and the patients age ranged between 19 and 78 years, averaging 48.0 years. Direct hernias were the most frequent with 44.6% cases. One hundred and fortyone (22.9%) operations were carried out in recurrence hernias. The overall rate of per and postoperative complications was 0.8% and 5.5%, respectively. Conversion to open repair was needed in 2 cases(0.32%) and the recurrence occurred in 4 patients (0.65%). Conclusions: the laparoscopic technique TAPP was shown to be safe and effective in the treatment of inguinal hernia in adults with high level of patient satisfaction. Presented low morbidity and general complications, in number and severity. The minimum rate of recurrence appear, compares favorably to TAPP with other prosthetic tension free techniques, and should be incorporated ...